Cash transfers in Latin America: Effects on poverty and redistribution - Verónica Amarante; Martín Brun (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
In this paper, we present comparative evidence for eight Latin American countries regarding design and effects of cash transfers (CTs). On the basis of household survey data, we analyse their coverage, importance in household income, and effects on poverty reduction and income redistribution. We also present a static microsimulation to analyse the potential impacts of alternative programme designs including perfect targeting and higher budgets. Our results illustrate the wide variation of these interventions in terms of their design, coverage, and importance in household income. CTs account for a significant portion of household income in lower deciles. In spite of this, their effects in terms of reductions in the incidence, intensity, and severity of poverty are, in the best of cases, moderate and, although their progressivity is high, their redistributive impact is limited. These results are mainly explained by the meager resources involved. Even under perfect targeting, the budgets allocated to transfer programs in these countries would be insufficient to achieve full coverage in the lowest part of the income distribution.
Keywords: I38; 330; cash transfers; children; inequality; Latin America; poverty